2008
DOI: 10.1038/emboj.2008.178
|View full text |Cite
|
Sign up to set email alerts
|

NCAM-induced focal adhesion assembly: a functional switch upon loss of E-cadherin

Abstract: Loss of expression of the cell-cell adhesion molecule E-cadherin is a hallmark of epithelial-mesenchymal transition (EMT) in development and in the progression from epithelial tumours to invasive and metastatic cancers. Here, we demonstrate that the loss of E-cadherin function upregulates expression of the neuronal cell adhesion molecule (NCAM). Subsequently, a subset of NCAM translocates from fibroblast growth factor receptor (FGFR) complexes outside lipid rafts into lipid rafts where it stimulates the non-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
177
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 33 publications
(60 reference statements)
9
177
1
3
Order By: Relevance
“…Following TGF-β1 treatment, the TJP1 expression level was increased (1.86-fold) and TJP2 was decreased (0.54-fold). EMT additionally stimulates the expression of neural cell adhesion molecules, which interact with proto-oncogene Src family tyrosine kinase Fyn (FYN) to reduce inhibition of focal adhesion, migration and invasion (42). In the current study, the FYN protein expression levels were increased 1.45-fold.…”
Section: Discussionmentioning
confidence: 58%
“…Following TGF-β1 treatment, the TJP1 expression level was increased (1.86-fold) and TJP2 was decreased (0.54-fold). EMT additionally stimulates the expression of neural cell adhesion molecules, which interact with proto-oncogene Src family tyrosine kinase Fyn (FYN) to reduce inhibition of focal adhesion, migration and invasion (42). In the current study, the FYN protein expression levels were increased 1.45-fold.…”
Section: Discussionmentioning
confidence: 58%
“…It has recently been found that the loss of E-cadherin during EMT is associated with up-regulation of expression of CD56 in human epithelial breast carcinoma cells (9). The finding that CD56 is also up-regulated during mesodermal differentiation of hESCs suggests that CD56 is likely to be fundamental to the reorganization of cell assembly rather than specific to mesodermal commitment per se.…”
Section: Discussionmentioning
confidence: 79%
“…Although there are multiple genes associated with EMT progression, no reliable nonepithelial surface markers that identify cells undergoing this process have been reported to date. It was recently reported that the loss of E-cadherin expression during EMT is associated with up-regulation of neuronal cell adhesion molecule (NCAM)/ CD56 in human epithelial breast carcinoma cells (9). Ablation of CD56 expression inhibited cell spreading and EMT, whereas forced expression of CD56 resulted in epithelial cell delamination and migration (9).…”
mentioning
confidence: 99%
“…PolySia-specific retargeting also resulted in effective adenoviral infection of polySia-expressing human tumors in vitro and in vivo (e.g., SCLC, neuroblastoma, and rhabdomyosarcoma). PolySia is also an attractive molecular target because it is associated with malignant features (20)(21)(22). Furthermore, the high degree of tumor selectivity promises a lower risk for offtarget infection.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent function of polySia is the regulation of cell-cell contacts because the presence of this negatively charged molecule on the cell surface promotes intercellular repulsion. Accordingly, polySia expression has been correlated with metastatic potential and epithelial-to-mesenchymal transition (21,22). The prevalence of polySia on invasively growing tumors is associated with poor clinical prognosis (20), and the absence in healthy peripheral tissues makes it an attractive molecular target for oncolytic adenovirus retargeting.…”
Section: Introductionmentioning
confidence: 99%